Pengembangan LKPD berbasis pendekatan saintifik berbantuan geogebra - Amalia, Fitriyany Nailul; Muhammad Ghiyats Ristiana; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to determine the feasibility, practicality and effectiveness of the product being developed. The product developed is a Student Worksheet (LKPD) on flat-sided building materials based on an assisted scientific approach GeoGebra. This research uses the method Research and Development (R&D), the 4D model according to Thiagarajan is limited to 3 stages, namely definition, design and development. The instruments used are test and non-test instruments. Data is processed using Microsoft Excel 2010. The subjects in the research were class VIII students at one of the Cimahi State Middle Schools, totaling 36 students in the limited trial and 72 students in the wide trial. The feasibility of the LKPD developed during validation obtained very valid results. The results of the practicality test in the limited trial were categorized as practical and in the extensive trial it was found to show the very practical category. The results obtained from the effectiveness of the LKPD showed that it was in the very effective category. Based on the research conducted, the results of the LKPD are shown flat-sided spatial building material based on an assisted scientific approach GeoGebra declared feasible, practical and effective for use.